(untitled) (Bangladesh Veterinarian, 2018)
This study investigated outbreaks of Foot and Mouth Disease (FMD) in cattle in Pabna district, Bangladesh, during August-September 2015. Out of 100 cattle, 45 were infected with FMD virus, of which five young and two adult cattle died and the postmortem changes in internal organs were recorded. Oral tissue samples from infected cattle (n = 20) of four Upazillas (Sub-district) of Pabna district were collected for viral RNA extraction and serotype identification using reverse transcriptase polymerase chain reaction (RTPCR). Gross and histopathological changes in oral, pedal and mammary tissues were typical of FMD. Characteristics lesion of ’tiger heart disease’ was seen in heart muscle of young and adult cattle. There was thickening of interlobular septum of lungs and characteristics of interstitial pneumonia. The uniplex and multiplex RT-PCR detected FMD viruses (430 bp) and FMD viral serotypes “O” (402 bp) and “Asia 1” (292 bp). Cattle of Sujanagar, Chatmahar and Isshardi Upazillas of Pabna district were infected with FMD viral serotype “O” and responsible for mortality of three young and two adult cattle. FMD viral serotype “Asia 1” causing death of two young cattle at Pabna Sadar. The fragment (485 bp) of Vp1 gene of FMD viral serotype “O” sequenced showed mutation in main antigenic sites. The phylogenetic analysis carried out with the Vp1 gene of FMD viral serotype “O” showed the viruses belonging to ME-SA topotype. The death of young and adult cattle was probably due to cardiac and/or respiratory failure. The adapted RTPCR protocol can be used in practice for detecting FMD viruses and its serotyping. Larger samples sizes require investigating to identify existing FMD viral serotypes and topotypes in order to design future preventive strategies. Bangl. vet. 2016. Vol. 33, No. 2, 39-50